2019
DOI: 10.1088/1742-6596/1246/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Preanesthetic maternal anxiety of 0 – 12 years old children who will undergo anesthesia and the contributing factors

Abstract: Emotional stress, such as seen in preanesthetic anxiety, often occurs in parents and children who will undergo surgery and anesthesia. Preanesthetic anxiety is a subjective feeling associated with increased autonomic nervous system activity. Preanesthetic anxiety experienced by parents can be passed onto their children and have a negative impact on a child such as the occurrence of post anesthesia behaviour disorders. In Indonesia, data about preanesthetic maternal anxiety is still unavailable. The purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
0
1
Order By: Relevance
“…Perdana et al reported a negative correlation between maternal level of education and anxiety before her child undergoes surgery. However, the younger the age of child, the higher the anxiety (15). However, in our study, no statistically significant difference was found between pediatric patients divided into 4 different age groups in terms of their mother's anxiety and depression scores (p = 0.227, p = 0.777, respectively).…”
Section: Discussioncontrasting
confidence: 75%
“…Perdana et al reported a negative correlation between maternal level of education and anxiety before her child undergoes surgery. However, the younger the age of child, the higher the anxiety (15). However, in our study, no statistically significant difference was found between pediatric patients divided into 4 different age groups in terms of their mother's anxiety and depression scores (p = 0.227, p = 0.777, respectively).…”
Section: Discussioncontrasting
confidence: 75%